Distinct sulfur saturation histories within the Palaeogene Magilligan Sill, Northern Ireland: Implications for Ni-Cu-PGE mineralisation in the North Atlantic Igneous Province - Lindsay, JJ; Hughes, HSR; Smyth, D; McDonald, I; Boyce, AJ; Andersen, JCØ (Canadian Journal of Earth Sciences, 2019)
This is the author accepted manuscript. The final version is available from NRC Research Press via the DOI in this record. The ~60 m thick Magilligan Sill is part of the British Palaeogene Igneous Province in the North Atlantic. The sill comprises layers of dolerite and olivine gabbro, and it intrudes a thick sequence of Mesozoic mudstones and marls, which are locally baked at the sill margins. Since 2014, the sill has been an exploration target for orthomagmatic Ni-Cu-PGE sulfide mineralisation analogous to the Noril’sk-Talnakh intrusion in Russia. We present new petrological, geochemical and S-isotope data to assess the prospectivity of the sill and the underlying magmatic plumbing system. Most sulfides in the dolerite portions of the sill are < 50 μm in size and comprise only pyrite with PGE abundances below detection limit. In the olivine gabbros, > 150 μm size pentlandite, chalcopyrite and pyrrhotite grains contain < 4 ppm total PGE, 1 460 ppm Co and 88 ppm Ag. Pyrite from the dolerites have δ34S ranging from -10.0 to +3.4 ‰ and olivine gabbro sulfides range from -2.5 to -1.1 ‰, suggesting widespread crustal contamination. The S/Se ratios of sulfides in the dolerites and olivine gabbros range from 3 500 to 19 500 and from 1 970 to 3 710, respectively, indicating that the latter may have come from upstream in the magma plumbing system. The Magilligan Sill records multiple injections of mafic magma into an inflating sill package, each with distinct mechanisms towards S-saturation. Whilst the sulfide minerals in the sill do not constitute significant mineralisation themselves, detailed in-situ studies highlight a divergence in Ssaturation histories, and suggest that a larger volume of olivine gabbro sulfides at depth may be prospective.